SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A method to identify positive tipping points to accelerate low-carbon transitions and actions to trigger them - Timothy M. Lenton; Thomas W. R. Powell; Steven R. Smith; Frank W. Geels; Floor Alkemade; Martina Ayoub; Pete Barbrook-Johnson; Scarlett Benson; Fenna Blomsma; Chris A. Boulton; Joshua E. Buxton; Sara M. Constantino; et al. (Sustainability Science, 2026)
Meeting the Paris Agreement to limit global warming to “well below 2 °C” requires a radical acceleration of action, as the global economy is decarbonising at least five times too slowly. Tipping points, where low-carbon transitions become self-propelling, could be key to achieving the necessary acceleration. We deem these normatively ‘positive’, because they can limit considerable, inequitable harms from global warming and help achieve sustainability. Some positive tipping points, such as the UK’s elimination of coal power, have already been reached at national and sectoral scales. The challenge now is to credibly identify further potential positive tipping points, and the actions that can bring them forward, whilst avoiding wishful thinking about their existence, or oversimplification of their nature, drivers, and impacts. Hence, we propose a methodology for identifying potential positive tipping points, assessing their proximity, identifying the factors that can influence them, and the actions that can trigger them. Building on relevant research, this ‘identifying positive tipping points’ (IPTiP) methodology aims to establish a common framework that we invite fellow researchers to help refine, and practitioners to apply. To that end, we offer suggestions for further work to improve it and make it more applicable.

Multi-instrument sounding of a Jovian thunderstorm from Juno - Shawn R. Brueshaber; Zhimeng Zhang; John H. Rogers; Gerald Eichstädt; Glenn S. Orton; Davide Grassi; Leigh N. Fletcher; Cheng Li; Shinji Mizumoto; Alessandro Mura; Fabiano Oyafuso; Ramanakumar Sankar; et al. (Icarus, 2025)

Alkali metal depletion in the deep Jovian atmosphere: The role of anions - Yury S. Aglyamov; Sushil K. Atreya; Ananyo Bhattacharya; Cheng Li; Steven Levin; Scott J. Bolton; Michael H. Wong (Icarus, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Super-adiabatic temperature gradient at Jupiter's equatorial zone and implications for the water abundance - Cheng Li; Michael Allison; Sushil Atreya; Shawn Brueshaber; Leigh N. Fletcher; Tristan Guillot; Liming Li; Jonathan Lunine; Yamila Miguel; Glenn Orton; Paul Steffes; J. Hunter Waite; et al. (Icarus, 2024)

Laboratory measurements of the 15–46 cm wavelength opacity of water vapor under temperature conditions characteristic of the deep atmosphere of Jupiter - Paul G. Steffes; Amadeo Bellotti; Mark D. Sprouse; Kyle G. Phillips; Daniel G. Gerges; Pablo Cembellin; Steven M. Levin; Scott J. Bolton (Icarus, 2023)

Finding incident cancer cases through outpatient oncology clinic claims data and integration into a state cancer registry - Christopher R. Cogle; Gary Levin; David J. Lee; Steven Peace; Megsys C. Herna; Jill MacKinnon; Clement K. Gwede; Celeste Philip; Tara Hylton (Cancer Causes & Control, 2021)

The Origin of NOAA’s Integrated Ecosystem Assessment Program: A Retrospective and Prospective - Chris J. Harvey; David L. Fluharty; Michael J. Fogarty; Phillip S. Levin; Steven A. Murawski; Franklin B. Schwing; Rebecca L. Shuford; Christopher R. Kelble; Mark E. Monaco (Coastal Management, 2021)

Opportunities for agent‐based modelling in human dimensions of fisheries - Matthew G. Burgess; Ernesto Carrella; Michael Drexler; Robert L. Axtell; Richard M. Bailey; James R. Watson; Reniel B. Cabral; Michaela Clemence; Christopher Costello; Chris Dorsett; Steven D. Gaines; Emily S. Klein; et al. (Fish and Fisheries, 2020)
Models of human dimensions of fisheries are important to understanding and predicting how fishing industries respond to changes in marine ecosystems and management institutions. Advances in computation have made it possible to construct agent‐based models (ABMs)—which explicitly describe the behaviour of individual people, firms or vessels in order to understand and predict their aggregate behaviours. ABMs are widely used for both academic and applied purposes in many settings including finance, urban planning and the military, but are not yet mainstream in fisheries science and management, despite a growing literature. ABMs are well suited to understanding emergent consequences of fisher interactions, heterogeneity and bounded rationality, especially in complex ecological, social and institutional contexts. For these reasons, we argue that ABMs of human behaviour can contribute significantly to human dimensions of fisheries in three areas: (a) understanding interactions between multiple management institutions; (b) incorporating cognitive and behavioural sciences into fisheries science and practice; and (c) understanding and projecting the social consequences of management institutions. We provide simple examples illustrating the potential for ABMs in each of these areas, using conceptual (“toy”) versions of the POSEIDON model. We argue that salient strategic advances in these areas could pave the way for increased tactical use of ABMs in fishery management settings. We review common ABM development and application challenges, with the aim of providing guidance to beginning ABM developers and users studying human dimensions of fisheries.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Regime shifts in a social-ecological system - Steven J. Lade; Alessandro Tavoni; Simon A. Levin; Maja Schlüter (Theoretical Ecology, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)